Irradiated mesenchymal stem cells support stemness maintenance of hepatocellular carcinoma stem cells through Wnt/β-catenin signaling pathway - Jing Hou (Cell & Bioscience, 2020)
Abstract Background Cancer stem cells are the main reason of relapse, metastasis and resistance to anti-cancer therapies of Hepatocellular carcinoma (HCC). Mesenchymal stem cells (MSCs) are an important part of the tumor microenvironment. MSCs have been demonstrated to be involved in drug resistance in tumor. How MSCs contribute to radiotherapy resistance of HCC is still indistinct. Methods Flow cytometry analysis was performed to isolate CD133+ cells from HCC cell lines Huh7 and PLC. The stemness of Huh7-CD133 and PLC-CD133 those were co-cultured with IR-MSCs were investigated by Colony formation assay. Tumor formation in nude mice was used to explore the tumorigenicity of CD133+ cancer cells. The activating Wnt/β-catenin signaling pathway in CSCs were also detected by RT-PCR and Western blotting. Results We report that irradiated MSCs (IR-MSCs) could increase the ratio of CD133+ cells in hepatocellular carcinoma cells. IR-MSCs could promote stemness maintenance of HCC stem cells. After co-cultured with IR-MSCs, liver cancer stem cells (CSCs) presented increased colony formation ability and tumor formation ability. We also found IR-MSCs promoted Wnt expression of CSCs. Reverse suppression experiment showed that when Wnt inhibitor was added into the culture medium, the effect of IR-MSCs on stemness maintenance was counteracted. Conclusions These data showed that IR-MSCs could support stemness maintenance of CSCs by activating Wnt/β-catenin signaling pathway.